IMPLEMENTASI KURIKULUM MUATAN LOKAL Dl SEKOLAH - Suyitno Al., Suyitno Al. (Jurnal Cakrawala Pendidikan, 2016)
The eletnenta~ye ducation's Local Content Curriculuii (LCC), initiated in 1987 and renewed in 1994, whicli constitutes 20% of the National Curriculum, has the strategic hnction of giving elementary education the content or color that will make it fit the needs ofregional development. LCC will result in students who understand the problems of dcvelopment in their area. The implementation of LCC all this time has been very limited because of various constraints. 'The constraiilts p;lrtl) come from the limited capabilities of schools. the lack of support from tlie Department of Education and Culture, and the utideveloped cooperation between schools and the surrounding community. Culture need to take are conducting teachers' upgrading, providing facilities, and assisting tlie develotiient of cooperation between one school and another and between schools and society or other relevant institutions. The i~iiprovement on the quality of LCC's implementation at schools will hopefully produce students who understand the potentials and needs of regional develop~nenat nd possess useful basic skills so that they can participate in tlie national development.